EFEKTIVITAS PENDEKATAN SCIENTIFIC DENGAN METODE OBSERVASI DAN DISKUSI DALAM MENINGKATKAN CAPAIAN BELAJAR DAN KINERJA SISWA KELAS VII SMP KRISPA SILIAN - Inggrit Octavia Akay; Djeli Alvi Tulandi; Jimmy Lolowang (Program Studi Pendidikan Fisika Jurusan Fisika Fakultas Matematika, Ilmu Pengetahuan Alam, dan Kebumian (FMIPAK), Universitas Negeri Manado, 2021)
The first step to learn science is through observation and measurement as a part of the observation. The research was conducted with the aim to improve the processes and student learning outcomes by implementing the teaching through the application of a scientific approach to the method of observation and discussion on the subject of